Risk factors for diarrhea in a cohort of dairy heifer calves reared in individual outdoor hutches in Piraí, Rio de Janeiro, Brazil - Fagundes, Thais Ferreira; Vidal, Letícia Gabriela Poblete; Alves, Pedro Afonso Moreira; Tassinari, Wagner de Souza; Menezes, Rita de Cássia Alves Alcântara de; Fonseca, Adevair Henrique da; Pereira, Maria Julia Salim (Semina: Ciências Agrárias, 2016)
This study aimed to evaluate the association between diarrhea and risk factors potentially related to diarrhea incidence, such as Cryptosporidium, Giardia, Eimeria and nematode infection, animal age, failure to transfer passive immunity, type of fertilization (artificial insemination - AI, in vitro production of embryos - IVP and natural breeding), mother (heifer/cow) and birth weight of heifer calves reared in individual outdoor hutches on a dairy farm. The database used in the present study refers to a weekly survey of a cohort of 118 heifer calves from birth to 100 days of age. A logistic generalized additive model (GAM) was fit to evaluate the functional relationship between the risk of diarrhea occurrence and birth weight. For analysis purposes, the database was divided into calves up to 30 days old and calves 31 to 100 days old. Bivariate and multivariate analyses were performed using logistic regression models via generalized estimating equations. All variables were included in the models and were removed oneby-one according to Wald statistics to obtain the final model. The relative risks (RR) and their respective 90% confidence intervals were estimated. The final model for calves up to 30 days old showed that IVP [RR=0.33 (90% CI 0.14; 0.75)] is a protective factor and that Cryptosporidium spp. infection [RR=1.95 (90% CI 1.22; 3.12)] is a risk factor. Although not statistically significant [RR=1.46 (90% CI 0.98; 2.18)], failure to transfer passive immunity increases the risk of diarrhea. The final model for calves 31 - 100 days old showed that IVP [RR=0.50 (90% IC 0.28; 0.89)] and birth weight ? 40 kg [RR=0.65 (90% CI 0.47; 0.89)] are protective factors. In this age group, Cryptosporidium spp. infection has no statistical significance [RR=1.25 (90% CI 0.95; 1.64)]. These results indicate that some of the diarrhea episodes observed in animals up to 30 days old could be explained by Cryptosporidium infection; therefore, better monitoring of these animals is recommended. Greater care in colostrum administration is suggested because animals with hypoglobulinemia are more sensitive to diarrhea occurrence. Although attention should be given to all animals with a low birth weight, special care should be given to those 31 to 100 days old.